Rationale and design of the EU-CERT-ICD prospective study: comparative effectiveness of prophylactic ICD implantation - Zabel, Markus; Sticherling, Christian; Willems, Rik; Lubinski, Andrzej; Bauer, Axel; Bergau, Leonard; Braunschweig, Frieder; Brugada, Josep; Brusich, Sandro; Conen, David; Cygankiewicz, Iwona; Flevari, Panagiota; et al. (ESC heart failure, 2019)
AIMS: The clinical effectiveness of primary prevention implantable cardioverter defibrillator (ICD) therapy is under debate. The EUropean Comparative Effectiveness Research to Assess the Use of Primary ProphylacTic Implantable Cardioverter Defibrillators (EU-CERT-ICD) aims to assess its current clinical value. METHODS AND RESULTS: The EU-CERT-ICD is a prospective investigator-initiated non-randomized, controlled, multicentre observational cohort study performed in 44 centres across 15 European Union countries. We will recruit 2250 patients with ischaemic or dilated cardiomyopathy and a guideline indication for primary prophylactic ICD implantation. This sample will include 1500 patients at their first ICD implantation and 750 patients who did not receive a primary prevention ICD despite having an indication for it (non-randomized control group). The primary endpoint is all-cause mortality; the co-primary endpoint in ICD patients is time to first appropriate shock. Secondary endpoints include sudden cardiac death, first inappropriate shock, any ICD shock, arrhythmogenic syncope, revision procedures, quality of life, and cost-effectiveness. At baseline (and prior to ICD implantation if applicable), all patients undergo 12-lead electrocardiogram (ECG) and Holter ECG analysis using multiple advanced methods for risk stratification as well as detailed documentation of clinical characteristics and laboratory values. Genetic biobanking is also organized. As of August 2018, baseline data of 2265 patients are complete. All subjects will be followed for up to 4.5 years. CONCLUSIONS: The EU-CERT-ICD study will provide a necessary update about clinical effectiveness of primary prophylactic ICD implantation. This study also aims for improved risk stratification and patient selection using clinical and ECG risk markers.
Keywords: výsledek terapie; dilatační kardiomyopatie; Risk factors; Electrocardiography; hodnocení rizik; kvalita života; Cardiomyopathy, Dilated; Sudden cardiac death; Quality of Life; Risk Assessment; výběr pacientů; Survival Rate; primární prevence; následné studie; Mortality; Europe; Death, Sudden, Cardiac; Prospective Studies; Implantable cardioverter defibrillator; náhlá srdeční smrt; Defibrillators, Implantable; Patient Selection; Follow-Up Studies; Primary Prevention; Treatment Outcome; Evropa; lidé; Humans; defibrilátory implantabilní; míra přežití; elektrokardiografie; prospektivní studie